Antiretroviral Therapy Availability and HIV Disclosure to Spouse in Rakai, Uganda: A Longitudinal Population-Based Study. (1st June 2015) - Haberlen, Sabina A.; Nakigozi, Gertrude; Gray, Ronald H.; Brahmbhatt, Heena; Ssekasanvu, Joseph; Serwadda, David; Nalugoda, Fred; Kagaayi, Joseph; Wawer, Maria J.
Abstract : Background: A decade after the rollout of antiretroviral therapy (ART) in sub-Saharan Africa, the effects of this structural change on social aspects of HIV, such as rates of HIV disclosure to partners, remain largely unmeasured. We evaluated whether the introduction of ART was associated with disclosure of HIV diagnosis to spouses in Rakai, Uganda, using longitudinal, population-based data. Methods: We identified individuals in marital/cohabitating unions who were newly diagnosed with HIV in Rakai Community Cohort Study surveys between 2000 and 2008, where ART was introduced in mid-2004. Using discrete-time survival analysis, we assessed the hazard of self-reported HIV disclosure to spouse after diagnosis pre-ART and post-ART rollout, adjusting for individual and union characteristics. Disclosure in the ART period was further stratified by ART initiation. Results: The analysis included 557 married adults, 264 of whom were diagnosed with HIV before ART was available (2000–2004), and 293 diagnosed after ART was introduced (2005–2008). The cumulative incidence of self-reported disclosure was 75.2% in the post-ART period, compared with 58.3% before ART availability [ P < 0.001, adjusted hazard ratio: 1.46 (95% confidence interval: 1.16 to 1.83)]. In the post-ART period, observed disclosure rates were 39% (72 of 184) among those not in HIV care, 65% (82 of 126) among those in pre-ART care, and 85% (64 of 75) among persons on ART ( P < 0.001). Conclusions: Treatment availability and use, especially ART initiation, was associated with increased self-disclosure of HIV diagnosis to partners. ART access may facilitate the prevention of transmission to uninfected partners and linkage to treatment for infected couples.